REGIONAL TRANSFORMATIONS IN SOUTHEAST ASIA AND THE PROBLEM OF JUST REGIONAL (AND WORLD) ORDER - E. V. Koldunova (Сравнительная политика, 2019)
The diachronic comparative analysis of the regional orders in Southeast Asia in pre-colonial, colonial and post-colonial periods presented in the article allows to demonstrate that despite their subordinate position in the international system Southeast Asian states not only managed to adopt themselves to the nation-state concept but also to develop their own regional instruments of raising their international profile. Alongside with this adaptation the indigenous (pre-colonial) perceptions of the regional order were becoming less relevant in terms of international relations and became the domain of socio-political and philosophical thought. The paper argues that the experience of collective action of Southeast Asian states united in ASEAN and the necessity to accommodate a variety of intraregional and wider international limitations resulted in a quite objective and rational view of a desired just regional order. Its core assumptions imply inclusiveness, acceptance of the nation-state-based international system, adherence to the shared norms and principles. They also indicate regional desire to see a lower Western interventionism but not the Western decline in the international system. As for China, Southeast Asian state perceive it as desirable strong economic, but not political force. ASEAN Outlook on the Indo-Pacific reflect this approach. However justified it seems, there are still open questions concerning the instruments of its implementation.